Central Banking in the Philippines: Then, Now and the Future - Mario B. Lamberte (Philippine Institute for Development Studies (PIDS), 2002)
The countrys central bank has a profound impact on the lives of all residents in the country. This paper attempted to put some policy issues on central banking in the country in certain perspectives so that policy debates on these issues can proceed with greater focus. More specifically, it examined central banking in the Philippines from three perspectives the past, the present and the future. First, it took a fresh look at central banking in the Philippines in the last 25 years. This period, which covers 5 administrations and 6 central bank governors, is the most turbulent period in the history of central banking in the Philippines. Second, the paper examined the way the Bangko Sentral ng Pilipinas (BSP) currently conducts monetary policy, highlighting the BSPs shift to inflation targeting as its monetary policy framework and the issues it must confront to make it successful. Third, it discussed the future of central banking in the Philippines, taking into account three major trends that are currently sweeping around the world, namely, the separation of bank supervision function from monetary policy function of central banks, increasing regional economic and financial integration, and the revolution in the payments system brought about by rapid changes in information and communications technology. These factors can lead to changes in the fundamental character of the countrys central bank in the future.
Keywords: 330; central bank; monetary policy; Bangko Sentral ng Pilipinas; inflation targeting; Zentralbank; Geldpolitik; Inflationssteuerung; Philippinen